1-(7-cloroquinolin-4-il)-5-metil-n-fenil-1H-1,2,3-triazol-4 carboxamida, tem efeito na melhora da memória e na epileptogênese em camundongos - Vogt, Ane Gabriela (2021)
As the scope of treatment options for neurological diseases is limited, it is necessary to search for new agents that help prevent the worsening of these diseases. In this sense, quinoline-derivative compounds attract the attention of the scientific community, due to their pharmacological activities. Thus, the aim of this study was to investigate the possible neuroprotective effect of the compound 1-(7-chloroquinolin-4-yl)-5-methyl-N-phenyl-1H-1,2,3-triazole-4- carboxamide (QTCA-1) against memory deficit and epileptogenesis. In the present study, male Swiss mice were used and were evaluated (i) the anticholinesterase action of QTCA-1 in vitro, as well as the effect of acute treatment of the compound in the different phases of memory (acquisition, consolidation and retrieval) in amnesic mice; (ii) the anti-aminesic activity of QTCA-1, in a sub-chronic model, related to dementia in mice, as well as evaluating the involvement of the cholinergic system, the activity of Na+/K+- ATPase and the oxidative damage in brain structures from mice induced by scopolamine (SCO); in addition (iii) the effect of QTCA-1 on the severity of seizures, oxidative stress and memory disorders in a model of kindling induction by pentylenetetrazol (PTZ) in mice, as well as the role of the enzymes Na+/K+- ATPase and of acetylcholinesterase (AChE) in mice brain structures (cerebral cortex and hippocampus). It was possible to verify that QTCA-1 (i) modulated the cholinergic system, through the inhibition of AChE activity in vitro in the cerebral cortex and hippocampus of mice, as well as attenuated the alterations caused by SCO in the different phases of memory (acquisition, consolidation and retrieval) in the inhibitory avoidance test, not causing changes in the locomotor and exploratory activity of the animals; (ii) demonstrated anti-amnesic effect in a subchronic model, through normalization of AChE and Na+/K+- ATPase activities as well as oxidative damage in cerebral structures modified by SCO; (iii) attenuated epileptogenesis and memory deficit, as well as oxidative damage and Na+/K+-ATPase activity in brain structures, in a PTZ- induced kindling model. In conclusion, this quinoline derivative seems to exert neuroprotective action in improving memory and epileptogenesis mainly by modulating oxidative damage and Na+/K+-ATPase activity. Furthermore, the effect of QTCA-1 also seems to be linked to the anticholinesterase activity of the compound.